Influence of time of aplication of growth regulators on boll retention and seed set of upland cotton (Gossypium hirsutum) and tree cotton (Gossypium arboreum) crosses - BAISAKH, B; KHANNA, V K; RAJ, B (The Indian Journal of Agricultural Sciences, 2013)
The effect of gibberellic acid (GA3) and indole acetic acid (IAA) on boll retention and seed set in crosses of upland cotton (Gossypium hirsutum L.) and tree cotton (Gossypium arboreum L.) was studied during 1994-95 after applying these growth regulators individually and in combination on flower at emasculation, at the time of pollination and 48 hr after pollination. Maximum interspecific crossed bolls were obtained in spring when GA3 (100 ppm) was applied in ’Vikas’ x ’Lohit’ and reciprocal. In rainy season similar trend was observed for boll retention. Maximum interspecific crossed seed was obtained by application of GA3 (100 ppm) in spring and rainy seasons. The best time of growth regulators application was at pollination in both the seasons.